Defining the upper extremity range of motion for safe automobile driving. (May 2018) - Rawal, Aziz; Chehata, Ash; Horberry, Tim; Shumack, Matthew; Chen, Chao; Bonato, Luke
Abstract: Background: There are no guidelines for return to driving following upper extremity injury. A greater comprehension of the role of the upper extremity in driving is required to assist clinicians in their fitness-to-drive assessments. This research aims to assist clinicians by analyzing the motion at the upper extremity in safe automobile driving. Methods: Thirty-six participants were recruited to the Monash University Accident Research Centre's driving simulator. They were tested in a realistic driving simulation using highway scenarios and traffic hazards. An OptiTrack™ motion tracking system recorded participants' upper limb movements. Findings: The following ranges of motion were recorded (left and right arm mean whole numbers): The shoulder flexed from 14 to 54°, abducted to 18°and adducted to 9°. Shoulder rotation ranged from 6° external to 32° internal rotation. Elbow flexion ranged from 35° to 72°. Pronation reached 77° and supination to 24°. Wrist flexion reached 34° and extension reached 23°. The wrist deviated to 17°radially and 38° ulnar. To avoid simulated hazards, the steering wheel revolved 57.2° (SD 19.2). The key movements in hazard avoidance are shoulder flexion, shoulder rotation, forearm rotation and wrist deviation. Interpretation: Shoulder flexion, internal rotation and forearm rotation have been shown to be key upper extremity movements in safe driving. Clinicians can refer to the ranges of motion recorded in this investigation, or the driving task at hand in their fitness-to-drive assessments. The ability to revolve the steering wheel 100° exceeds the 95th percentile of the steering wheel revolution angle required to avoid simulated traffic hazards. Highlights: The role of the upper extremity in automobile driving is not well understood. The motional requirements of the upper limb are recorded in a driving simulator. The range of motion at the upper extremity in driving varies considerably. Shoulder flexion and rotation, and forearm rotation are key in safe driving. Revolving the steering wheel 100° is a suggested rehabilitation target.